วงก่วนกว๊าดมอญ : ดนตรีชุมชนมอญ บ้านวังกะหมู่ 2 ตำบลหนองลู อำเภอสังขละบุรี จังหวัดกาญจนบุรี - ทัพวิเศษ อภิชาติ (Journal of Fine and Applied Arts Khon Kaen University, 2015)
The purposes of study are to investigate Wong Kuan-Kward Mon : Mon local music at Wong-Ga village, Moo 2 Nong-Lu sub-district, Sangkhlaburi district, Kanchanaburi province.The purposes of this research are to study community culture,cultural characteristics, the musical performance and songs according to ethnomusicology methodology. This is a field study through surveying, interviewing and analyzing the information during 2007-2009 A.D. The research reveals as follows : 1.The Wong Kuan-Kward-Mon is a musical performance of the Mon community composing of four groups of musical instrument. Those instruments are 1) Pluck Instrument :Ja-Yam(Zeither). 2)Bowed Instrument : Ka-Yo-Horn(Viloin). 3)Struck Instrument : Pat-Ka-La(Wooden Xylophone), Pat-Ka-La-Pa-Sol(Mental Xylophone),Pat-Khan(Gong). Wang-chorn( 21 drums). 4)Blow Instrument : Kha-nau(Oboe),Ta-Lhod(Blowhold) and Percussion Instrument : Ha-Pern-Ha-Nhok(Big drum),Ha-Pern(Small drum).Pern-Mang(4 drums),Ka-Dee,Ha-Nerd(Graw),Chan(Cymbal).The Wong Kuan-Kward-Mon influenced on Monûs culture and tradition including Mon important celebrating festivals at Wong-Ga village, The performance impressed Mon ethnics in inspiring the community to preserve their traditional living, dressing, religious believes, ceremony and dialect as well as in uniting the feeling of the communityûs proud of ethnic and strength among the villagers. 2. The songs are inherited from the Mon musical instructors in Burma and accompanied with instruments during the performance in the auspicious occasion of their communityûs traditional ceremonial days and also in cultural seminars of external authorities and organizations.